(untitled) (Universal International Scientific Journal, 2026)
This article describes the impact of destructive behavior on the Internet on social stability. In modern society, the Internet is not only an information technology, but also a complex social reality that shapes ideological, cultural and moral processes. The Internet is becoming an indicator not only of external threats (fund propaganda, foreign political manipulation), but also of internal social instability and spiritual gaps. In particular, unorganized youth, women and unemployed strata are falling under the influence of certain ideological groups.